Youth Religious Development Nurul Jannah Mosque Perum Tas III Kepuh Kemiri Village, Tulangan District - Rizky Eka Meyko Saputro; Anita Puji Astutik (Universitas Muhammadiyah Sidoarjo, 2021)
Adolescents are a period of entering puberty, the puberty period experienced by them as the beginning of the emergence of inner turmoil that really needs a mental shelter that is able to provide a positive direction in the development of further life to direct teenagers to positive things. the attitude of youth, for example, youth participation in commemorating major holidays is a good opportunity to activate youth in Islamic activities. The purpose of this study was to determine the religious development of youth at Masjid Nurul Jannah Perum TAS III Kepuh Kemiri Village, Tulangan District. This research includes qualitative research. The subjects in this study were mosque takmir, community leaders, mosque youth. the types of data sources obtained are primary data sources and secondary data sources. Data collection techniques are by means of observation, interviews, and documentation. Data analysis and interpretation techniques are data reduction, data presentation and conclusion drawing or data verification. The results of this study have shown its effectiveness in the success of religious development. This can be proven by the existence of self-awareness in adolescents who are increasingly participating in congregational prayers and participating in other religious activities